Synthesis of Zinc oxide nanoparticles (ZnO NPs) using aqueous leaf extract of Zanthoxylum armatum DC for photocatalytic degradation of Organic dye: Plant-mediated synthesis and characterization of ZnO nanoparticles for photocatalytic and antimicrobial applications (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Plant-mediated production of ZnO NPs is explored in this study, namely the use ofZanthoxylum armatum DC. leaf extract as a reducing and capping agent. UV-Vis, UV-DRS, FTIR, FESEM,EDS, and TEM were all used to analyse the produced ZnO NPs. Degradation of a model organic dyepollutant (MB) was used to examine the photocatalytic activity of ZnO NPs when exposed to UVirradiation from a metal halide lamp (70.2 W• m-2 UV and 452.5 W•m-2 visible irradiation intensity). ZnONPs produced in a lab were tested for their antioxidant properties using DPPH radical. In addition, Grampositive(Bacillus subtilis) and Gram-negative (Escherichia coli) harmful bacteria were tested forsusceptibility to green produced ZnO NPs antimicrobial activity.